A Meta-Analysis of Studies on Quality Assessment of Public Libraries Using the LibQUAL Model - Reza Karimi; Mohammad Asadzadehbaghi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی)
Purpose: Given the importance of assessing the quality of public libraries and their different services, this study aimed to comprehensively review the existing research in this field and present the findings in the form of a meta-analysis. The primary goal of this meta-analysis was to combine and compare the results of studies conducted on public libraries using the LibQUAL model through statistical meta-analysis methods to achieve applicable and cohesive results. Methodology: This research employed a library-based data collection approach and a meta-analysis technique for data analysis. The statistical population of this study included studies conducted on public libraries using the LibQUAL model from 2009 to 2020. A total of 25 articles and theses available in scientific databases were selected, and after evaluation based on inclusion criteria, 17 studies with a defined population, sample size, sampling method, and usage of the LibQUAL model were analyzed. Data collection tools included relevant studies and a meta-analysis coding form. Comprehensive Meta-Analysis Software (CMA 2) was used for calculating coefficients. Findings: According to the funnel plot and Begg and Mazumdar's rank correlation method, there was no publication bias in the reviewed studies. Additionally, the Q index for six research variables and overall I2 statistic indicators indicated that the studies are heterogeneous. The adjusted standardized difference between the maximum and received mean effect sizes, considering the random model, showed large effect sizes and negative differences of -1.13 in the service effect at maximum, medium effect size and positive difference of +0.66 in the service effect at minimum, large effect size and negative difference of -2.2 in information access at maximum, large effect size and negative difference of -0.14 in information access at minimum, large effect size and negative difference of -2 in the library as a place at maximum, and large effect size and negative difference of -0.02 in the library as a place at minimum. Overall, the total maximum effect size was large with a negative difference of -1.77, and the total minimum effect size was large with a positive difference of +0.16. Originality/Value: The results indicate that public libraries, except in the minimum service variable, perform poorly in all variables and fail to meet the minimum expectations of public library users. They do not offer satisfactory and ideal services in almost all dimensions. Additionally, given the substantial sample size and low error rate in studies on these three variables according to Cohen's d index, the findings of research on public libraries using the LibQUAL tool can be considered highly reliable. It is suggested that public library institutions focus more on information and communication technologies and related equipment to facilitate access, create websites, provide printed journals and electronic resources and meet user needs to achieve the highest level of user satisfaction.